Implementasi Pemasaran Lembaga Pendidikan Melalui Trial Class SMP Al Furqan Ditinjau Dari Kerangka Marketing Mix 7P - Mohammad Fikri Hamdani; Suwandi Suwandi (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze in depth the implementation of educational institution marketing strategies through the online Trial Class program at SMP Al Furqan MQ Tebuireng Jombang through the lens of the 7P Services Marketing Mix framework, as well as to measure its effectiveness in converting public interest into actual new student enrollment decisions. The approach used in this study is descriptive qualitative with a field research case study design, where data were intensively gathered in April 2026 through a combination of triangulation techniques, including limited participant observation of virtual instructional processes, in-depth interviews with 6 key informants (the principal, public relations coordinator, practicing teachers, and parents), and authentic documentation analysis, which were subsequently processed using the Miles and Huberman interactive model. The findings demonstrate that the integration of the 7P marketing mix into the Trial Class program yielded a highly significant quantitative impact, whereby out of a total accumulation of 365 active elementary school student participants, 207 students (56.71%) officially converted into registered new students, thereby dominating 95.39% of the institution's official new student enrollment capacity. The scientific novelty of this research lies in the tactical formulation modifying traditional "Place" elements into digital ecosystems (Zoom and WhatsApp) combined with the packaging of a miniature "3 in 1" curriculum (classical tahfidz Al-Qur'an and modern science based on SEAQIS standard STEM) as a free "Price" core product to break down psychological barriers to entry and overcome the intangibility of Islamic boarding school services through the seamless, original, and interconnected fulfillment of David A. Kolb's Experiential Learning Cycle stages.